1989
DOI: 10.1007/bf00250565
|View full text |Cite
|
Sign up to set email alerts
|

Structural inhomogeneity in the neuropil of lamina II/III in rabbit visual cortex

Abstract: Due to the bundling of apical dendrites throughout laminae IV-II of the cerebral cortex, two compartments of neuropil are distinguished: (1) the neuropil of the dendrite bundles consisting of closely associated, vertically oriented apical dendrites of pyramidal cells and the fine cell processes between them and (2) the neuropil separating the dendrite bundles. The aim of the present study is to obtain more information concerning differences in composition and arrangement of fine cell processes in the two compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…From an earlier stereological study of the upper half of lamina II/III at the ultrastructural level it is known that the volume fraction of extracellular space is about 30% larger in the neuropil between bundles, than in the compartments of dendrite bundles (Schmolke and Schleicher 1989). Together with the data of the present study which has revealed that the relative amount of neuropil between bundles in the lower half of lamina II/III is higher than that in the upper half of lamina II/III (cf.…”
Section: Extracellular Spacementioning
confidence: 99%
See 4 more Smart Citations
“…From an earlier stereological study of the upper half of lamina II/III at the ultrastructural level it is known that the volume fraction of extracellular space is about 30% larger in the neuropil between bundles, than in the compartments of dendrite bundles (Schmolke and Schleicher 1989). Together with the data of the present study which has revealed that the relative amount of neuropil between bundles in the lower half of lamina II/III is higher than that in the upper half of lamina II/III (cf.…”
Section: Extracellular Spacementioning
confidence: 99%
“…This contradiction can only be explained by taking into account the effect of tortuosity upon electrical conductivity, which is contrary to that of the size of extracellular space. The fact that the neuropil between bundles mainly consists of submicroscopically small cell processes running in all directions, whereas the dendrite bundles comprise a large proportion of thick, vertically oriented cell processes (Schmolke and Schleicher 1989), might indicate that the degree of tortuosity of the extracellular space is higher in the neuropil between bundles than in the dendrite bundles. If this assumption is true, the tortuosity of extracellular space would be higher in the lower than in the upper half of lamina II/III.…”
Section: Extracellular Spacementioning
confidence: 99%
See 3 more Smart Citations